Aspects Regarding the Traceability in Temperature Measurements - Andreea-Diana MOROŞANU; Madalina Elena MILITARU; Gabriel Marius DUMITRU (The Annals of “Dunarea de Jos” University of Galati. Fascicle IX, Metallurgy and Materials Science, 2016)
The traceability of national standards to a reference measurement is essential to correctly translate the information about customer preferences described in international standards as a prerequisite which exists for the design of goods that comply with the expected characteristics. The traceability of national and reference measurement standards to the International System (S.I.) is achieved by: comparisons with the primary measurement standards of other countries and periodic calibration with respect to measurement standards of other international and national institutes of metrology, whose traceability to the SI is already proven and widely recognized internationally. This paper discusses how traceability is possible or it is ensured in temperature measurements, by using measuring instruments that are traceable at International Temperature Scale of 1990 (ITS-90) [1].